Manganese oxide and zinc oxide doped graphene electrode material and preparation method and application thereof

CN123002833APending Publication Date: 2026-10-30HAINAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611265831.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

色谱及光谱类方法通常具有较高的准确性和灵敏度,但往往存在检测周期长、样品前处理步骤复杂、依赖昂贵仪器设备等问题,从而在现场快速检测和便携式应用方面受到一定限制

Benefits of technology

本发明提供的MnOx-ZnO-LIG电极材料通过激光诱导一步法在PI基底上实现MnOx-ZnO和多孔石墨烯同步生成,制备过程简便、成本低廉,避免了现有检测方法中需要昂贵仪器和复杂前处理的缺陷,且操作简单,适合非专业人员快速检测。本发明制备MnOx-ZnO-LIG电极材料的过程中形成的金属氧化物与碳骨架之间存在界面电子相互作用,有利于优化界面电荷分布并加快电子传输速率。并且,原位生成的多孔三维结构显著提升了材料的电活性表面积,为电解质的充分接触与目标分子的富集提供了更多有效反应位点,从而进一步增强电极材料的电催化响应能力。同时,本发明基于MnOx-ZnO-LIG作为工作电极材料界面,并结合便携式电化学工作站,构建了左氧氟沙星电化学传感器。结果表明,本发明提供的电化学传感器对左氧氟沙星检测限为5.46 nmol/L,线性范围为2×10-5-0.3 mmol/L。在测定实际样品中左氧氟沙星的含量时加标回收率为96.0-98.30%。本发明提供的电极材料制备方法简单、易操作,与便携式传感器和手机相连接,即可得到柔性便携式电化学传感器,具有优异的检测性能和良好的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002833A_ABST
    Figure CN123002833A_ABST
Patent Text Reader

Abstract

The application discloses a manganese oxide and zinc oxide doped graphene electrode material and a preparation method and application thereof, and belongs to the technical field of electrochemical sensors. x As a working electrode material interface, and combined with a portable electrochemical workstation, an electrochemical sensor for levofloxacin is constructed.The electrode material preparation method is simple and easy to operate, and the flexible portable electrochemical sensor can be obtained by connecting the portable sensor and a mobile phone, and has excellent detection performance and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical sensor technology, and particularly relates to a manganese oxide and zinc oxide doped graphene electrode material, its preparation method and application. Background Technology

[0002] Levofloxacin (LEV) is an important quinolone antibiotic used not only to treat human bacterial infections but also for the prevention and treatment of animal diseases in livestock and aquaculture. LEV easily leaves residues in animal-derived foods and environmental water bodies, potentially posing a threat to human health. Therefore, LEV is recognized as an emerging environmental pollutant, posing a threat to the ecological environment and public health. Based on this, providing a sensitive and selective method for LEV detection is of great significance for safeguarding public health and environmental safety.

[0003] To date, researchers have reported various detection techniques for LEVs, including high-performance liquid chromatography (HPLC), chemiluminescence immunoassay (CPI), fluorescence spectroscopy, and electrochemical analysis. While chromatographic and spectroscopic methods generally offer high accuracy and sensitivity, they often suffer from long detection cycles, complex sample pretreatment steps, and reliance on expensive instruments, thus limiting their application in rapid on-site detection and portable systems. In contrast, electrochemical analysis methods have attracted widespread attention due to their ease of operation, rapid response, low equipment cost, and ease of miniaturization and portability. Especially with the continuous development of nanomaterial-modified electrodes, electrochemical technology has achieved improvements in sensitivity, detection limits, and applicability to practical samples, providing a new technological pathway for the rapid and efficient detection of LEVs.

[0004] Therefore, how to provide a rapid and efficient electrochemical analysis method for detecting LEVs is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a manganese oxide and zinc oxide-doped graphene electrode material, its preparation method, and its application.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a graphene electrode material doped with manganese oxide and zinc oxide includes the following steps: After mixing and dispersing carbon precursor, manganese source and zinc source, the mixture is coated onto a substrate and dried to obtain a manganese-zinc doped carbon precursor film. The manganese oxide and zinc oxide doped graphene electrode materials are then prepared in situ by laser etching.

[0007] Preferably, the carbon precursor is polyamic acid (PAA).

[0008] Preferably, the zinc source is zinc chloride (ZnCl2); The manganese source is manganese chloride (MnCl2).

[0009] Beneficial effects: This invention employs a method of pre-doping manganese and zinc salt precursors uniformly into a polyimide (PI) carbon precursor, followed by laser-induced one-step in-situ preparation of MnO. x / ZnO / LIG composite flexible electrode material. Compared with traditional multi-step hydrothermal, growth, drop-coating and high-temperature calcination methods, this invention does not require additional loading of active materials and complex post-processing. The preparation process is simple, short, and low-cost. Furthermore, PI carbonization and in-situ metal salt conversion can be completed simultaneously during laser induction, enabling MnO to... x The uniform anchoring of ZnO nanoparticles within the LIG three-dimensional porous framework enhances the bonding strength between the active component and the conductive substrate, avoiding the problem of active material detachment in traditional drop-coating methods. This significantly improves the mechanical stability and long-term stability of the electrode material.

[0010] Manganese oxide (MnO) x MnO exhibits variable valence states, and its abundant redox active sites and excellent electrocatalytic performance enable it to demonstrate good selectivity and high sensitivity in the detection of small organic molecules. Furthermore, MnO with different crystal phases and valence states... x Materials such as MnO, MnO2, and Mn3O4 exhibit differentiated electron / ion migration capabilities and surface reactivity during electrochemical reactions, making them promising candidates for electrocatalysis, molecular adsorption, ion exchange, biosensing, and energy storage. This invention introduces zinc oxide (ZnO), a typical n-type semiconductor material with a wide bandgap (3.37 eV), high electron mobility, and excellent chemical stability. ZnO nanostructures not only provide rapid electron transport channels at the electrode interface but also promote the adsorption and electron transfer of target molecules through their abundant surface active sites, accelerating the interfacial electron transfer process and enhancing the structural stability of the electrode material, thus playing a synergistic reinforcing role in the composite system.

[0011] Preferably, the molar ratio of the manganese source to the zinc source is 0.37:0.15.

[0012] Beneficial effect: When the molar ratio of manganese source to zinc source is 0.37:0.15, the resulting composite material has the largest electrochemical response current.

[0013] Preferably, the coating thickness is 25-35 μm.

[0014] Beneficial Effects: This coating thickness ensures the formation of a uniform and dense film of the polyimide precursor on the substrate surface, and facilitates full carbonization during laser-induced formation to create a continuous three-dimensional porous LIG structure. When the coating thickness is less than 25 μm, the precursor content is insufficient, resulting in an incomplete LIG structure and low active material loading, which is detrimental to improving electrochemical response. When the coating thickness is greater than 35 μm, laser energy struggles to penetrate the entire film, easily leading to insufficient carbonization and localized ablation of the material, affecting the conductivity and structural uniformity of the composite material. Therefore, controlling the coating thickness within the range of 25-35 μm is beneficial for obtaining MnO with a complete structure, excellent conductivity, and abundant active sites. x The / ZnO / LIG composite electrode improves the electrochemical detection performance and reusability of the electrode.

[0015] Preferably, the drying process involves first drying at 90-110℃ for 25-45 minutes, and then drying at 150-170℃ for 8-15 minutes.

[0016] Beneficial effects: First drying (90-110℃): Gently removes residual solvent; prevents rapid evaporation of solvent at high temperatures, which can cause blistering, cracking, and peeling of the film; ensures a uniform and dense film.

[0017] The second drying process (150-170℃) further removes residual solvent from deeper layers; promotes partial imidization (cyclization) of PAA (polyamic acid) to PI (polyimide); enhances the mechanical stability and heat resistance of the film, facilitating subsequent laser etching; and provides a suitable pre-carbonization structural state, resulting in higher and more uniform carbonization efficiency during laser printing. Direct high-temperature rapid heating causes rapid evaporation of the internal solvent, leading to blistering and cracking of the film; uneven surface carbonization increases defects in the laser-induced graphene (LIG) pattern formed during laser printing. Therefore, this invention employs a two-stage drying process.

[0018] Preferably, the output power of the laser etching is 1.1-2.75W.

[0019] Beneficial effects: Compared with traditional carbonization methods, laser etching offers significant advantages such as low cost, high precision, template-free operation, and rapid in-situ generation. During laser induction, the laser instantaneously generates high temperatures and rapidly cools, introducing abundant microscopic defects and active sites onto the material surface, significantly improving the specific surface area and electrochemical activity of the electrode material.

[0020] A manganese oxide and zinc oxide-doped graphene electrode material prepared by the method described above.

[0021] Beneficial effects: MnO obtained by the above preparation method xIn ZnO-LIG electrode materials, MnO x The uniform in-situ anchoring of ZnO nanoparticles onto the surface of a laser-induced three-dimensional porous graphene framework forms a tightly bonded composite structure. This not only effectively prevents the shedding of active components and improves the mechanical and long-term stability of the material, but also facilitates the utilization of MnO. x The synergistic catalytic effect between ZnO and the material accelerates interfacial electron transport, improves the electrocatalytic activity and conductivity of the material, and provides an excellent electrode material for constructing high-performance electrochemical sensors.

[0022] An electrochemical sensor comprising the aforementioned manganese oxide and zinc oxide-doped graphene electrode materials.

[0023] Preferably, the working electrode of the electrochemical sensor comprises a manganese oxide and zinc oxide-doped graphene electrode material, and the reference electrode is a silver electrode.

[0024] Beneficial effects: This invention uses MnO x Using the ZnO-LIG composite material as the working electrode can fully utilize its excellent conductivity, abundant electrocatalytic active sites, and large specific surface area to improve the enrichment capacity of target molecules and electron transport efficiency. Using the silver electrode as the reference electrode has the advantages of potential stability, simple preparation, low cost, and easy integration, which can ensure good repeatability and stability of the sensor detection process, thereby realizing rapid and sensitive detection of levofloxacin.

[0025] Application of an electrochemical sensor in the detection of levofloxacin.

[0026] Beneficial effects: This invention utilizes MnO x -ZnO-LIG electrochemical sensors are used for levofloxacin detection, which can fully utilize MnO x The synergistic electrocatalytic effect of ZnO and the advantages of the LIG three-dimensional conductive network enable rapid and highly sensitive detection of levofloxacin. This detection method requires no complex sample pretreatment, is fast, simple to operate, and low in cost. It also features a wide linear detection range, a low detection limit, good selectivity, repeatability, and stability.

[0027] Compared with the prior art, the present invention has the following advantages and technical effects: The MnO provided by this invention x -ZnO-LIG electrode material was fabricated on a PI substrate using a laser-induced one-step method to achieve MnO. x The simultaneous generation of ZnO and porous graphene is a simple and inexpensive preparation process that avoids the drawbacks of existing detection methods that require expensive instruments and complex pretreatment. Furthermore, its ease of operation makes it suitable for rapid detection by non-professionals. This invention also prepares MnO. xThe metal oxides formed during the ZnO-LIG electrode material production process exhibit interfacial electronic interactions with the carbon framework, which optimizes interfacial charge distribution and accelerates electron transport rates. Furthermore, the in-situ generated porous three-dimensional structure significantly increases the electroactive surface area of ​​the material, providing more effective reaction sites for sufficient electrolyte contact and target molecule enrichment, thereby further enhancing the electrocatalytic response of the electrode material. Simultaneously, this invention is based on MnO... x A levofloxacin electrochemical sensor was constructed using ZnO-LIG as the working electrode material interface and combined with a portable electrochemical workstation. Results showed that the electrochemical sensor provided by this invention has a detection limit of 5.46 nmol / L for levofloxacin and a linear range of 2 × 10⁻⁶. -5 -0.3 mmol / L. The recovery rate of levofloxacin in actual samples was 96.0-98.30%. The electrode material preparation method provided by this invention is simple and easy to operate. By connecting it to a portable sensor and a mobile phone, a flexible portable electrochemical sensor can be obtained, exhibiting excellent detection performance and good stability. Attached Figure Description

[0028] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 (A) SEM image of LIG obtained in Comparative Example 1; (BC) SEM image of MnO obtained in Example 1. x Scanning electron microscope images of ZnO-LIG at different magnifications; Figure 2 MnO prepared in Example 1 x Transmission electron micrographs of ZnO-LIG at different magnifications; Figure 3 MnO prepared in Example 1 x SEM-mapping plot of ZnO-LIG; Where A is MnO x - SEM image of ZnO-LIG; B. Overall elemental distribution map; C. Zinc mapping; D. Carbon mapping; E. Oxygen mapping; F. Manganese mapping; Figure 4 MnO obtained in Example 1 x X-ray diffraction patterns of ZnO-LIG and LIG obtained in Comparative Example 1; Figure 5 MnO obtained in Example 1 x(A) XPS full spectrum of ZnO-LIG, and (B) high-resolution XPS spectra of C 1s, (C) Mn 2p and (D) Zn 2p; Figure 6 The detection results of levofloxacin by the electrochemical sensor assembled from the electrode materials prepared in Examples 1-4; Wherein, A represents the detection results of levofloxacin after applying the electrochemical sensor obtained in Examples 1-4; B represents the detection results of levofloxacin in different buffer solutions using the electrochemical sensor obtained in Example 1; C represents the detection results of levofloxacin under different pH conditions using the electrochemical sensor obtained in Example 1; D represents E... pc A schematic diagram illustrating the linear relationship with pH; Figure 7 The results (A), linearity (B), anti-interference results (C), and stability results (D) of using the electrochemical sensor obtained in Example 1 to detect different concentrations of levofloxacin are shown. Figure 8 To compare the LIGE obtained in Application Example 1 and the MnO obtained in Application Example 1 x -ZnO-LIGE (A) Qt curve; (B) Q and t 1 / 2 A linear relationship; Figure 9 In Example A, the electrochemical behavior of the electrode material prepared in Example 1 with levofloxacin is compared with that of LIGE obtained in Example 1, ZnO-LIGE obtained in Example 2, and MnO obtained in Example 3. x -LIGE and MnO obtained from Application Example 1 x CV curve of ZnO-LIGE in 0.1 mol / L Tris-HCl solution; B represents the LIGE obtained in Comparative Application Example 1, the ZnO-LIGE obtained in Comparative Application Example 2, and the MnO obtained in Comparative Application Example 3. x -LIGE and MnO obtained from Application Example 1 x CV curves of ZnO-LIGE in 1.0 mmol / L K3[Fe(CN)6] and 0.5 mol / L KCl; Figure 10 For comparison, the LIGE obtained in Application Example 1, the ZnO-LIGE obtained in Application Example 2, and the MnO obtained in Application Example 3 are compared. x -LIGE and MnO obtained from Application Example 1 x CV curve of ZnO-LIGE in a solution containing 0.25 mmol / L LEV; Figure 11 MnO x- Preparation of ZnO-LIGE (A) and MnO x-Schematic diagram of LEV detection by ZnO-LIGE (B); Figure 12 The CV curves of the electrodes obtained in Application Example 1 and Comparative Application Examples 4-6 in 0.25 mmol / L LEV solution are shown. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0031] Unless otherwise specified, all raw materials used in the embodiments of this invention were purchased through commercial channels; The polyamic acid (PAA) was purchased from Dongguan Zhangmutou Suyuan Plastic Raw Material Business Department, and the model is thermosetting DMAC / PI; Unless otherwise specified, room temperature or normal temperature in the embodiments of the present invention refers to 25±3℃.

[0032] Example 1 A method for one-step laser-induced preparation of manganese oxide-doped graphene electrode material includes the following steps: (1) Take 4.0 g of PAA carbon precursor solution with a mass concentration of 20%, add 200 µL of ethanol solution containing 0.37 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2, and sonicate for 10 min to achieve full and uniform dispersion to obtain a polyamic acid solution doped with MnCl2·4H2O and ZnCl2; coat the polyamic acid solution doped with MnCl2·4H2O and ZnCl2 onto a glass plate (coating thickness is 30 μm), first place it in a vacuum drying oven at 100℃ for 30 min, and then place it in an oven at 166℃ for 10 min to obtain a polyimide film doped with manganese chloride and zinc chloride (MnCl2-ZnCl2-PI). (2) Laser etching was performed on MnCl2·4H2O and ZnCl2-doped polyimide films. The output power of the laser direct writing instrument was set to 2.2W to prepare manganese oxide (MnO) in situ. xLaser-induced graphene (LIG) of zinc oxide (ZnO) is used to form electrode materials on a glass plate. The working electrode is then removed from the glass plate to obtain a manganese oxide and zinc oxide-doped graphene electrode material (MnO). x -ZnO-LIG).

[0033] Example 2 The only difference from Example 1 is that the output power of the laser direct writing instrument in step (2) is 1.10W, specifically including the following steps: Step (1) is the same as in Example 1; (2) Laser etching was performed on MnCl2·4H2O and ZnCl2-doped polyimide films. The output power of the laser direct writing instrument was set to 1.10W to prepare manganese oxide (MnO) in situ. x Laser-induced graphene (LIG) of zinc oxide (ZnO) is used to form electrode materials on a glass plate. The working electrode is then removed from the glass plate to obtain a manganese oxide and zinc oxide-doped graphene electrode material (MnO). x -ZnO-LIG).

[0034] Example 3 The only difference from Example 1 is that the output power of the laser direct writing instrument in step (2) is 1.65W, specifically including the following steps: Step (1) is the same as in Example 1; (2) Laser etching was performed on MnCl2·4H2O and ZnCl2-doped polyimide films. The output power of the laser direct writing instrument was set to 1.65W to prepare manganese oxide (MnO) in situ. x Zinc oxide (ZnO) laser-induced graphene (LIG) electrode material (MnO) x -ZnO-LIG).

[0035] Example 4 The only difference from Example 1 is that the output power of the laser direct writing instrument in step (2) is 2.75W, specifically including the following steps: Step (1) is the same as in Example 1; (2) Laser etching was performed on MnCl2·4H2O and ZnCl2-doped polyimide films. The output power of the laser direct writing instrument was set to 2.75W to prepare manganese oxide (MnO) in situ. x Laser-induced graphene (LIG) of zinc oxide (ZnO) was used to form a working electrode on a glass plate. The working electrode was then removed from the glass plate to obtain a manganese oxide and zinc oxide-doped graphene electrode material (MnO). x -ZnO-LIG).

[0036] Application Example 1 A method for preparing a manganese oxide-doped graphene electrode includes the following steps: A silver paste with a thickness of 15 μm was uniformly coated onto the desired area of ​​the electrode surface obtained in Example 1 to form a reference electrode pattern. Subsequently, it was heated and cured at 140 °C for 20 min to obtain a manganese oxide-doped graphene electrode, denoted as MnO. x -ZnO-LIGE.

[0037] Application Example 2-4 The only difference from Application Example 1 is that the electrode material obtained in Example 1 is replaced with the electrode material obtained in Examples 2-4 (corresponding to Application Examples 2-4). All other process steps and parameters are the same as in Application Example 1.

[0038] Comparative Example 1 A method for preparing a graphene electrode, differing from Example 1 only in that step (1) does not include a manganese source and a zinc source, specifically including the following steps: (1) Take 4.0 g of PAA carbon precursor solution with a mass concentration of 20% and coat it on a glass plate (coating thickness of 30 μm) to form a precursor film. First, place it in a vacuum drying oven and dry it at 100℃ for 30 min to remove the solvent. Then, place it in a constant temperature oven and dry it at 166℃ for 10 min to achieve partial imidization reaction and obtain polyimide film (PI). (2) Laser etching is performed on the polyimide film. The output power of the laser direct writing instrument is set to 2.2W. Laser-induced graphene (LIG) is prepared in situ. A working electrode is formed on the glass plate. The working electrode is removed from the glass plate to obtain the graphene electrode material (LIG).

[0039] Comparative Example 2 The only difference from Example 1 is that the ethanol solution containing 0.37 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2 in step (1) is replaced with an equal volume of ethanol solution containing 0.15 mol / L ZnCl2. All other process steps and parameters are the same as in Example 1. This is denoted as ZnO-LIG.

[0040] Comparative Example 3 The only difference from Example 1 is that the ethanol solution containing 0.37 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2 in step (1) is replaced with an equal volume of ethanol solution containing 0.37 mol / L MnCl2·4H2O. All other process steps and parameters are the same as in Example 1. (Note: The last part, "MnO", appears to be a typo and can be left as is.) x -LIG.

[0041] Comparative Example 4 The only difference from Example 1 is that the ethanol solution containing 0.37 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2 in step (1) is replaced with an equal volume of ethanol solution containing 0.10 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2. All other process steps and parameters are the same as in Example 1.

[0042] Comparative Example 5 The only difference from Example 1 is that the ethanol solution containing 0.37 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2 in step (1) is replaced with an equal volume of ethanol solution containing 0.40 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2. All other process steps and parameters are the same as in Example 1.

[0043] Comparative Example 6 The only difference from Example 1 is that the ethanol solution containing 0.37 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2 in step (1) is replaced with an equal volume of ethanol solution containing 0.20 mol / L MnCl2·4H2O and 0.15 mol / L ZnCl2. All other process steps and parameters are the same as in Example 1.

[0044] Comparative Application Example 1 The only difference from Application Example 1 is that the electrode material obtained in Example 1 is replaced with the electrode material obtained in Comparative Example 1. All other process steps and parameters are the same as in Application Example 1. This is denoted as LIGE.

[0045] Compare and contrast with example 2-3 The only difference from Application Example 1 is that the electrode material obtained in Example 1 is replaced with the electrode material obtained in Comparative Examples 2-3 (corresponding to Comparative Application Examples 2-3). All other process steps and parameters are the same as in Application Example 1, and the resulting electrodes are denoted as ZnO-LIGE (Comparative Application Example 2) and MnO, respectively. x -LIGE (Compare with application example 3).

[0046] Compare and apply examples 4-6 The only difference from Application Example 1 is that the electrode material obtained in Example 1 is replaced with the electrode material obtained in Comparative Examples 4-6 (corresponding to Comparative Application Examples 4-6). All other process steps and parameters are the same as in Application Example 1.

[0047] Technical effects: 1. Performance Characterization Figure 1 (A) SEM image of LIG obtained in Comparative Example 1; (BC) MnO obtained in Example 1x Scanning electron microscope images of ZnO and LIG at different magnifications; by Figure 1 Part A shows that LIG exhibits typical porous, network-like three-dimensional structural features. This structure is primarily attributed to the rapid carbonization of PI and the instantaneous release of gas during laser irradiation, resulting in a porous graphene structure. This porous structure provides abundant transport channels for ion migration and forms a highly efficient active interface between the material and the electrolyte, effectively enhancing the contact area between the electrode and the target molecules. Figure 1 As shown in sections B and C, MnO x The ZnO-LIG surface exhibits a porous, three-dimensional network structure with loaded particles, indicating that the composite material was successfully prepared.

[0048] Figure 2 Transmission electron microscopy (TEM) images of the MnOx-ZnO-LIG prepared in Example 1 at different magnifications; as shown Figure 2 As shown in sections A and B, the TEM images clearly show the morphology of the nanoparticles distributed on the LIG surface. Figure 2 The CE section shows the characteristic lattice fringes of the nanoparticles. Specifically, the lattice spacing of 0.24 nm corresponds to the (211) crystal plane of Mn3O4, 0.22 nm to the (111) crystal plane of MnO, and 0.25 nm to the (101) crystal plane of ZnO. These results indicate that MnCl2 and ZnCl2 transform into MnO during laser-induced processing. x And ZnO, and uniformly distributed on the LIG surface.

[0049] Figure 3 The image shows the SEM mapping of MnOx-ZnO-LIG prepared in Example 1; where A is a scanning electron microscope image; B is an elemental distribution map; C represents zinc; D represents carbon; E represents oxygen; and F represents manganese. Figure 3 It can be seen that the elements are evenly distributed; Figure 4 MnO obtained in Example 1 x The X-ray diffraction patterns of ZnO-LIG and LIG show that the LIG XRD pattern exhibits two relatively broad diffraction peaks at 25.2° and 43.6°, corresponding to the (002) and (100) crystal planes of graphitic carbon, respectively (JCPDF#41-1487), indicating that the material has a typical graphitized structure. MnO xThe XRD pattern of ZnO-LIG shows diffraction peaks at 35.9° and 62.2°, corresponding to the (211) and (400) crystal planes of Mn3O4 (PDF#13-0162), indicating the formation of Mn3O4. Diffraction peaks at 20.1°, 21.6°, and 58.6° correspond to the (100), (110), and (151) crystal planes of MnO (PDF#04-0326), indicating the formation of MnO. Meanwhile, the (002) and (100) characteristic peaks of graphitic carbon are still observed at 21.1° and 43.6°. Compared to LIG, MnO... x The leftward shift of the characteristic carbon peak in ZnO-LIG graphite indicates an increase in carbon interlayer spacing, which may be related to the introduction of metal oxides and their interfacial interaction with the carbon framework. This is because Zn... 2+ The amount of doping is small, and its corresponding crystal phase does not show obvious diffraction peaks in the XRD pattern.

[0050] Figure 5 The (A) MnO obtained in Example 1 x The XPS full spectrum of ZnO-LIG, and the high-resolution XPS spectra of (B) C 1s, (C) Mn 2p, and (D) Zn 2p, show that MnO x The XPS full spectrum of ZnO-LIG shows signal peaks for C 1s, N 1s, O 1s, Mn 2p, and Zn 2p, indicating that MnO x -ZnO-LIG contains C, N, O, Zn and Mn elements. Figure 5 The high-resolution C 1s spectrum shown in section B can be decomposed into four main peaks, located at approximately 284.8 eV, 285.5 eV, 288.4 eV, and 291.2 eV, which can be assigned to C=C, CO, OC=O, and C=O, respectively. Compared with the literature reports, the OC=O and C=O peaks shift towards higher binding energies, indicating a decrease in the electron cloud density around the carbon atom. This suggests a certain interfacial electronic interaction between the metal oxide and the carbon framework, thereby promoting charge transport and increasing the electron transport rate. Figure 5 The high-resolution spectrum of Mn 2p shown in section C contains two distinct characteristic peaks with binding energies of approximately 641.7 eV and 653.1 eV, respectively, corresponding to Mn 2p... 3 / 2 and Mn 2p 1 / 2 The positions of these peaks are consistent with those reported in the literature. Furthermore, a pair of Mn-associated peaks appear at approximately 642.8 eV and 654.7 eV. 3+ The characteristic peaks indicate the presence of Mn3O4 in the composite material. Figure 5 In the high-resolution spectrum of Zn 2p shown in section D, the two peaks appearing at approximately 1022.2 eV and 1044.8 eV correspond to Zn 2p, respectively.3 / 2 and Zn 2p 1 / 2 The position of the characteristic peak is consistent with that reported in the literature.

[0051] 2. Levofloxacin detection Assemble an electrochemical sensor using the electrode obtained in Application Example 1, including the following steps: The MnO obtained from Example 1 is applied. x -ZnO-LIGE was connected to an EmStat Blue portable electrochemical workstation to assemble an electrochemical sensor.

[0052] Levofloxacin was detected using the CV method in a 0.25 mmol / L levofloxacin solution at a scan rate of 0.1 V / s, with a potential range of 0.5 V–1.3 V. The peak current variation of the electrochemical sensor assembled using the electrodes obtained in Examples 1–4 was tested to determine the optimal laser output power for levofloxacin detection. The results are as follows: Figure 6 As shown in Part A of the diagram.

[0053] Depend on Figure 6 As shown in Part A, when the laser power increases from 1.10W to 2.20W, the peak current of FT (levofloxacin) gradually increases. When the laser power increases to 2.75W, the peak current of FT decreases, and the peak current of levofloxacin is highest at 2.20W. This is because the degree of graphitization of PI increases with increasing power. When the laser power is too high, it destroys part of the structure and chemical bonds of the LIG carbon layer, leading to a decrease in current value. Therefore, 2.20W was chosen as the optimal output power of the laser.

[0054] In a 250.0 μmol / L levofloxacin solution, the effects of different buffer solution types and pH values ​​on the electrochemical reaction detection of levofloxacin by the electrochemical sensor obtained in Example 1 were analyzed. The results are as follows: Figure 6 As shown in parts B and C, where, Figure 6 In Part B, four buffer solutions were selected: BR solution, PBS solution, HAc-NaAc solution, and Tris-HCl solution. Figure 6 In Part C, buffer solutions with Tris-HCl at pH values ​​of 6.0, 7.0, 8.0, and 9.0 were investigated.

[0055] Depend on Figure 6 As shown in Part B, among BR buffer solution, PBS solution, HAc-NaAc solution, and Tris-HCl solution, Tris-HCl buffer solution exhibited the highest current value, thus serving as the supporting electrolyte in the experiment. Simultaneously, CV curves were recorded for Tris-HCl buffer solutions at different pH values, as follows... Figure 6As shown in section C, the results indicate that the peak current increases with increasing pH until the solution reaches pH 7.0, and then decreases above pH 7.0. Furthermore, the levofloxacin peak potential shifts negatively with increasing pH, confirming the involvement of protons. Therefore, pH 7.0 was chosen as the optimal pH for further investigation. E pc It exhibits a good linear relationship with pH: E pc (V)=-0.055 pH+1.36 (γ=0.990) (eg Figure 6 (As shown in Part D). The slope of -55 mV / pH is very close to the theoretical value of Nernst (-59 mV / pH), which indicates that electrons and protons are transferred in equal numbers during the levofloxacin reaction.

[0056] 3. Drawing the working curve The optimal conditions were determined through the above tests, namely, using the electrochemical sensor obtained in Application Example 1, and detecting different concentrations of levofloxacin in a Tris-HCl buffer solution at pH 7.0 using cyclic voltammetry (CV). Simultaneously, the operating curve of the electrochemical sensor prepared under the optimal conditions was determined. The detection method includes the following steps: A 0.1 mol / L Tris-HCl buffer solution was used as the supporting electrolyte; the MnO obtained in Example 1 was applied. x The ZnO-LIGE electrochemical sensor was used as the working electrode for detection at room temperature. Scanning conditions: the scan voltage range was set to 0.7V-1.3V, and the scan rate was 0.1V / s. Test procedure: 25 μL of levofloxacin solutions (0.02, 0.5, 10, 50, 100, 150, 200, 250, and 300 μmol / L) were dropped onto the supporting electrolyte of the three-electrode system, respectively. Cyclic voltammetry (CV) was used for testing, and the reduction peak current values ​​under the corresponding CV curves were recorded. Results are as follows: Figure 7 As shown.

[0057] Figure 7 The electrochemical sensor assembled from the electrodes prepared in Example 1 detects different concentrations of levofloxacin (A) and shows the linear relationship (B). It can be seen that as the concentration of levofloxacin increases, the reduction peak current increases. Within the concentration range of 0.02 μmol / L–300 μmol / L, the corresponding regression equation is: I p (μA) = 834.413 C +14.889 (R 2 = 0.999), and the detection limit was 5.46 nmol / L (3S / N).

[0058] 4. Selectivity and stability The selectivity and stability of the electrochemical sensor obtained in Case 1 were tested. The test method included the following steps: Anti-interference test: Under room temperature conditions, tests were conducted using the same concentration of interfering substances (tetracycline, hydrazine hydrate) and twice the concentration of interfering substances (Mg). 2+ Na + and Fe 3+ The CV curves of 0.25 mmol / L LEV solution were obtained, and the current response values ​​under different conditions were recorded using the electrochemical sensor obtained in Application Example 1 to analyze the effect of interfering substances on the current response of levofloxacin detection.

[0059] Stability test: The electrochemical sensor obtained in Application Example 1 was sealed and stored at room temperature. It was taken out every day and the linear sweep voltammetry curve was measured in 250 μmol / L levofloxacin solution. The reduction peak current value was recorded. The test was conducted continuously for 5 days to evaluate the stability of the sensor.

[0060] The results are as follows Figure 7 As shown, Figure 7 Parts C and D show the anti-interference performance (C) and stability (D) of the electrochemical sensor obtained in Example 1, respectively. Part C shows that tetracycline, hydrazine hydrate, and Mg... 2+ Na + and Fe 3+ The effect on the detection of levofloxacin was minimal, indicating that the electrochemical sensor has good selectivity for levofloxacin. The electrochemical sensor obtained in Application Example 1 was stored in a sealed bag at room temperature, and the current values ​​of the CV curve were recorded daily in a 250 μmol / L levofloxacin solution. Figure 7 As shown in Figure D), all sensors exhibit similar current responses, with relative standard deviations all less than 5.00%, indicating that the sensor has good stability.

[0061] 5. Electroactive area Furthermore, the electroactive area of ​​the electrode prepared in Example 1 was tested by coulometric method in a mixed solution of 1 mmol / L K3[Fe(CN)6] and 0.5 mol / L KCl. The results are as follows: Figure 8 As shown.

[0062] Figure 8 To compare the LIGE obtained in Application Example 1 and the MnO obtained in Application Example 1 x -ZnO-LIGE (A) Qt curve; (B) Q and t 1 / 2 The linear relationship.

[0063] Depend on Figure 8 As can be seen from Part B, LIGE and MnO x -ZnO-LIGEQ and t 1 / 2 There is a good linear relationship. The linear regression equations are as follows: LIGE: Q (μC) = 44.209 t 1 / 2 (s 1 / 2 ) - 1.6406 (R 2 = 0.999); MnO x -ZnO-LIGE: Q (μC) = 104.238 t 1 / 2 (s 1 / 2 )+3.123 (R 2 = 0.998).

[0064] According to the above formula, LIGE and MnO x The effective area of ​​ZnO-LIGE is 0.146 cm². 2 and 0.344cm 2 MnO x The effective area of ​​-ZnO-LIGE is approximately 2.4 times that of LIGE.

[0065] 6. Electrochemical behavior The electrochemical behavior of the electrode prepared in Example 1 with levofloxacin was studied using CV analysis, and the results are as follows: Figure 9 As shown.

[0066] Figure 9 In Example A, the electrochemical behavior of the electrode prepared in Example 1 against levofloxacin is compared with that of the LIGE obtained in Example 1, the ZnO-LIGE obtained in Example 2, and the MnO obtained in Example 3. x -LIGE and MnO obtained from Application Example 1 x The CV curves of ZnO-LIGE in 0.1 mol / L Tris-HCl solution, B represents the comparative application examples LIGE obtained in Example 1, ZnO-LIGE obtained in Example 2, and MnO obtained in Example 3. x -LIGE and MnO obtained from Application Example 1 x CV curves of -ZnO-LIGE in 1.0 mmol / L K3[Fe(CN)6] and 0.5 mol / L KCl.

[0067] like Figure 9 As shown in Figure A, under a stable background current, LIGE, ZnO-LIGE, and MnO x -LIGE and MnO x-ZnO-LIGE did not exhibit any electrochemical response in a blank buffer solution. For example... Figure 9 As shown in Figure B, in 1.0 mmol / L K3[Fe(CN)6] and 0.5 mol / L KCl, compared with LIGE, ZnO-LIGE and MnO x -LIGE and MnO x The oxidation peak current of ZnO-LIGE increases sequentially, reaching 25.23 μA, 28.79 μA, and 37.04 μA, respectively. The corresponding reduction peak current also increases synchronously, indicating a gradual increase in electron transport efficiency. The oxidation peak potential shifts negatively, and... I pa / I pc The ratio is close to 1.05, exhibiting good redox symmetry. Meanwhile, the peak potential difference Δ... E p Reducing it to 0.10 V indicates that the reversibility of electrons in the electrode has been improved.

[0068] Figure 10 For comparison, the LIGE obtained in Application Example 1, the ZnO-LIGE obtained in Application Example 2, and the MnO obtained in Application Example 3 are compared. x -LIGE and MnO obtained from Application Example 1 x CV curve of ZnO-LIGE in a solution containing 0.25 mmol / L LEV.

[0069] like Figure 10 As shown, all four electrochemical sensors exhibited significant oxidation peaks, indicating that the oxidation process of levofloxacin on different modified electrodes is an irreversible reaction. The current intensity follows a pattern: [The text then abruptly shifts to a different topic:] Using the MnO obtained in Example 1... x -ZnO-LIGE (221.84 μA) > Compare with the MnO obtained in Application Example 3 x -LIGE (116.88 μA) > ZnO-LIGE obtained in Application Example 2 (104.06 μA) > LIGE obtained in Application Example 1 (85.81 μA). The results show that the MnO obtained in Application Example 1... x -ZnO-LIGE exhibits superior electrochemical performance.

[0070] To investigate the effect of MnCl2·4H2O concentration on MnO x The effect of different MnCl2·4H2O concentrations on the electrochemical detection performance of ZnO-LIG was evaluated by using different electrodes prepared in Application Example 1 and Comparative Application Examples 4-6 as working electrodes and performing cyclic voltammetry (CV) tests in 0.25 mmol / L LEV solution to record the changes in LEV oxidation peak current.

[0071] The results are as follows Figure 12 As shown in the figure, Application Example 1 and Comparative Application Examples 4-6 are referred to by the electrode materials used, with Example 1 representing Application Example 1 and Comparative Examples 4-6 representing Comparative Application Examples 4-6. Figure 12 It can be seen that as the concentration of MnCl2·4H2O gradually increases from 0.10 mol / L to 0.37 mol / L, the oxidation peak current of the prepared electrode for LEV gradually increases. In Application Example 1, the electrode prepared using the electrode material obtained in Example 1 with a concentration of 0.37 mol / L MnCl2·4H2O exhibits the highest peak current response, indicating that appropriately increasing the manganese source concentration is beneficial for promoting MnO oxidation. x The components are generated and form more synergistic catalytic active sites with ZnO. MnO x The multi-valence transition process in the LEV can promote electron transfer, and ZnO's excellent electron transport capability can further improve the interfacial charge transfer efficiency, thereby enhancing the electrocatalytic oxidation response of LEV molecules.

[0072] When the concentration of MnCl2·4H2O was further increased to 0.40 mol / L, the oxidation peak current of the electrode at LEV decreased. This may be because the excess manganese source caused MnO to... x Increased loading reduces the effective exposure of active sites and may also damage MnO. x An unbalanced ratio between MnCl2 and ZnO hinders electron transport, ultimately leading to a decrease in electrode catalytic activity. Therefore, a MnO concentration of 0.37 mol / L can achieve optimal catalytic activity. x The superior synergistic effect between the ZnO and ZnO provides optimal parameters for subsequent electrode fabrication.

[0073] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a graphene electrode material doped with manganese oxide and zinc oxide, characterized in that, Includes the following steps: After mixing and dispersing carbon precursor, manganese source and zinc source, the mixture is coated onto a substrate and dried to obtain a manganese-zinc doped carbon precursor film. The manganese oxide and zinc oxide doped graphene electrode materials are then prepared in situ by laser etching.

2. The method for preparing a manganese oxide and zinc oxide-doped graphene electrode material according to claim 1, characterized in that, The carbon precursor is polyamic acid.

3. The method for preparing a manganese oxide and zinc oxide-doped graphene electrode material according to claim 1, characterized in that, The zinc source is zinc chloride; The manganese source is manganese chloride.

4. The method for preparing a manganese oxide and zinc oxide-doped graphene electrode material according to claim 3, characterized in that, The molar ratio of the manganese source to the zinc source is 0.37:0.

15.

5. The method for preparing a manganese oxide and zinc oxide-doped graphene electrode material according to claim 1, characterized in that, The coating thickness is 25-35 μm.

6. The method for preparing a manganese oxide and zinc oxide-doped graphene electrode material according to claim 1, characterized in that, The drying process involves first drying at 90-110℃ for 25-45 minutes, and then drying at 150-170℃ for 8-15 minutes.

7. The method for preparing a manganese oxide and zinc oxide-doped graphene electrode material according to claim 1, characterized in that, The output power of the laser etching is 1.1-2.75W.

8. A graphene electrode material doped with manganese oxide and zinc oxide prepared by the preparation method as described in claim 1.

9. An electrochemical sensor, characterized in that, This includes the manganese oxide and zinc oxide-doped graphene electrode material as described in claim 8.

10. The application of the electrochemical sensor as described in claim 9 in the detection of levofloxacin.